2022
DOI: 10.3390/educsci12090635
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Knowledge Area on the Use of Digital Tools during the COVID-19 Pandemic among Latin American Professors

Abstract: In this paper, quantitative, descriptive, and correlational research is carried out on the impact that the process of digitalization of academic activities in higher education has had on the habits of use of information and communication technologies (ICT) among professors and the influence of the area of knowledge on this impact. For this purpose, responses from 716 professors from different Latin American universities to a survey designed by the authors were statistically analyzed. Following the UNESCO guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 96 publications
2
35
0
1
Order By: Relevance
“…The self-concept expressed by PA professors about their digital skills was low ( 2). These results are in line with the self-concepts of digital competence of profess the entire Latin American and Caribbean region [17,18,25,26], which shows that the no significant differences between the perceptions of digital competence of profess the PA countries with respect to professors in the countries of the region. The resul tained here show that professors' ratings of their digital skills are much more disp than the VR ratings (with a coefficient of variation of 41.26%, compared to variatio no more than 30% in the VR ratings).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The self-concept expressed by PA professors about their digital skills was low ( 2). These results are in line with the self-concepts of digital competence of profess the entire Latin American and Caribbean region [17,18,25,26], which shows that the no significant differences between the perceptions of digital competence of profess the PA countries with respect to professors in the countries of the region. The resul tained here show that professors' ratings of their digital skills are much more disp than the VR ratings (with a coefficient of variation of 41.26%, compared to variatio no more than 30% in the VR ratings).…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, the didactic usefulness of VR in higher education refers to its employability as a didactic resource, which not only involves technical knowledge of VR on the part of the professor, but also specific training in techno-pedagogical skills, availability of adequate spaces and technologies in universities, and access to these technologies by the entire educational community [17,18]. In this sense, the literature identifies deficient training in digital and techno-pedagogical competencies as one of the main limitations to the use of VR in lectures [19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts demonstrate that the gender gap in digital stress due to the pandemic and the digital competence of professors in different areas of knowledge are different in Venezuela and in countries with low GIIs: Bolivia, Honduras, and Guatemala. The specialized literature had already proved the existence of significant differences by professors’ area of knowledge in terms of professors’ digital competence [ 12 , 72 , 73 ], the digital stress derived from the pandemic [ 12 ], the impact of the pandemic on the frequency of use of digital technologies by professors [ 74 ], and the assessment of the use of digital tools in the classroom and the capacity of the teaching staff to adapt to them while maintaining a didactic perspective focused on student learning [ 75 , 76 , 77 ]. However, the description of the reasons that explain this difference in behavior exceeds the purposes of this paper, and they constitute an interesting line of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the integration of digital tools into the teaching processes in higher education and the consequent stress derived from it, studies from the literature have found that the area of a professor’s expert knowledge is a strongly explanatory variable. In this sense, the area of knowledge partially explains the levels of digital skills manifested by the professors [ 72 , 73 ], as well as the patterns of digital technology usage on their part [ 74 ]; it is more frequently used among professors of technical areas, who present higher levels of digital competence. However, a frequently indicated source of digital stress comes from the deficiency in teachers’ techno-pedagogical skills, for which their area of knowledge is not an explanatory variable [ 75 , 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%